Curcuminoids biosynthesis using synthetic biology approaches combined with a co-culture strategy - Rodrigues, Joana Lúcia Lima Correia (2022)
Curcuminoids are polyphenolic plant secondary metabolites extracted from the plant Curcuma longa. They have several therapeutic properties, including anti-cancer and anti-inflammatory activities. Curcumin, the most promising curcuminoid, holds an estimated market size of USD 151.9 million by 2027 and is very difficult and expensive to isolate from the other curcuminoids. Additionally, curcuminoids accumulate at low amounts in plants and the extraction process, besides being inefficient and expensive, is environmentally unfriendly and limited by seasonal variability. Therefore, in the past decade, several efforts have been made to produce curcuminoids using synthetic biology approaches [1-3]. We propose an optimized artificial biosynthetic pathway to produce curcuminoids in Escherichia coli [1]. This pathway involves six enzymes and produces ferulic acid as an intermediate. The curcuminoids pathway was divided in two modules, each module with three enzymes, where the first module produced ferulic acid from tyrosine and the second one produced curcuminoids from hydroxycinnamic acids. The optimization of the first module enabled obtaining the highest ferulic acid titer reported so far (1.3 mM). Afterwards, ferulic acid was used as substrate to optimize the second module of the pathway. We achieved the highest concentration of curcumin ever reported (1.5 mM), corresponding to a 59.4% increase [2]. Subsequently, curcuminoids were produced from tyrosine (with the whole pathway assembled in a single organism) in mono-culture. The production increased comparing to a previously reported pathway [3]. The potential of a co-culture strategy was also evaluated to further improve curcuminoids production by reducing the cells metabolic burden. We used one E. coli strain able to convert tyrosine to ferulic acid and another able to convert the hydroxycinnamic acids produced by the first strain to curcuminoids. Using the CRISPR-Cas9 technology we disrupted the -galactosidase gene in one of the strains which allowed to follow co-culture population composition using the blue-white screening method. The coculture strategies led to a 6.6 times increase of curcuminoids (125.8 M) when compared to the mono-culture system. The curcuminoids production achieved in this study corresponds to a 6817% improvement. To our knowledge, these values correspond to the highest titers of curcuminoids reported to date. These results demonstrate the enormous potential of modular co-culture engineering to produce curcuminoids from tyrosine.